Characteristics and Abundance of Large Microplastics in Sediments in Wonorejo Mangrove Tourism Area, Surabaya - Estina; Yona, Defri; Syarifah Hikmah Julinda Sari (Jurnal Biodjati, 2025)
Microplastic (MP) pollution is a growing environmental concern due to its persistence in aquatic ecosystems. Among MPs, large microplastics (1–5 mm) originate from the degradation of larger plastic debris and pose ecological risks. However, research on their accumulation in mangrove sediments remains limited. This study investigates the characteristics, abundance, and spatial distribution of large microplastics in the Wonorejo Mangrove Tourism Area, Surabaya, which receives plastic waste transported by the Wonorejo River. Surface sediment samples were collected from three stations, followed by drying, sieving, visual inspection, and Fourier Transform Infrared (FTIR) spectroscopy for polymer identification. The results indicate that film-type microplastics were the most abundant (72%), followed by fragments (23%) and pellets (5%). Transparent microplastics (38%) were the dominant color, followed by blue (26%). The highest microplastic concentration was recorded at Station 2 (130.7 ± 73.5 particles/kg), while Station 1 had the lowest (2.7 ± 2.7 particles/kg). Despite these variations, statistical analysis showed no significant differences in microplastic distribution among stations, suggesting a relatively homogeneous spatial pattern across the study area. FTIR analysis identified two dominant polymers: polypropylene (PP) and polyethylene (PE), commonly used in consumer and industrial products. The predominance of film-type microplastics and transparent coloration suggests that the primary sources of contamination are plastic bags and food packaging waste transported by river currents. These findings underscore the role of mangrove ecosystems as critical retention zones for plastic pollution, highlighting the urgent need for improved waste management strategies to mitigate microplastic accumulation in coastal environments.